A Descriptive Study to Determine the Serum and Salivary Uric Acid among Individuals With and Without Periodontitis - Uppin, Rabiya Basari (Asian Journal of Pharmaceutics (AJP), 2025)
To compare serum and salivary uric acid levels among adults suffering from and without periodontitis and to see their correlation with periodontal parameters. Materials and Methods: A cross-sectional study was conducted at a diagnostic center in Bidar, Karnataka, enrolling 316 adults (158 periodontitis cases and 158 controls) who underwent routine blood examination. Serum uric acid was assessed using a biochemical analyser, and sampling of unstimulated saliva followed for uric acid estimation. Various parameters such as personal characteristics (age, gender, smoking) and blood pressure, biochemical parameters (HbA1C, cholesterol, HDL, LDL, triglycerides), and periodontal parameters (plaque index, gingival index, probing pocket depth, clinical attachment loss) were recorded. Mann-Whitney test was used for comparison of uric acid levels between the two groups, and Spearman’s test assessed correlations. Results: Patients suffering from periodontitis exhibited significantly high serum uric acid (median = 6.30) as compared to the controls (median = 5.60; P < 0.001). On the same note, salivary uric acid in patients with periodontitis was also higher (median = 6.10) when compared to the control group (median = 4.80; P < 0.001). Serum uric acid positively correlated with probing pocket depth (r = 0.226, P < 0.001); however, salivary uric acid correlated even better (r = 0.402, P < 0.001). Elevation of triglycerides, diastolic blood pressure, and LDL contributed significantly to variation in uric acid (P < 0.05). Conclusion: Serum and salivary uric acid levels were elevated in patients suffering from periodontitis and correlated with its severity. Salivary urid acid may thus act as a good and reliable noninvasive biomarker for periodontitis.